Passive aeration of wastewater using tray aerators - El-Zahaby, Ayman Mostafa (AUC Knowledge Fountain, 2016)
Passive aeration units in water and wastewater treatment are aeration units that operate without the need for electric energy. They depend on dropping the water through the aerator, while increasing the surface area to volume ratio, and thus increasing the oxygen mass diffused into water. The passive units include cascade aerators, and tray aerators. On the contrary to cascade and spray aerators, tray aerators require a much smaller area for their installation. While researching the design of tray aerators, a shortage of literature pertaining to the topic was observed. The research objective is to develop a model for the design of tray aerators for the purpose of increasing the dissolved oxygen in wastewater. This thesis investigated the design parameters affecting the aeration performance of tray aerators for wastewater treatment plants. A mathematical model was developed that predicts the aeration performance of a tray aerator system as a function of the flow rate, number of trays, tray area, spacing between trays, number and diameter of holes per tray. Results illustrate that the aeration performance is directly proportional to the tray area, the spacing between trays, and number of trays and is inversely proportional to the flow rate. The number and diameter of holes together with the flow rate define the flow regime into dripping or jetting. The spacing between trays, the number and diameter of holes had slight effect on the aeration performance. The mass transfer coefficient (KL) is reported to be a variable rather than a constant figure. An empirical equation for the estimation of KL as a function in the spacing between trays, flow rate, and the total area of holes in the tray was developed from laboratory scale experiments. That equation is validated in the laboratory scale experiments, as well as in pilot scale application using real wastewater.